Pacing During and Physiological Response After a 12-Hour Ultra-Marathon in a 95-Year-Old Male Runner - Knechtle, Beat; Jastrzebski, Zbigniew; Rosemann, Thomas; Nikolaidis, Pantelis T. (Frontiers in Physiology, 2019)
In recent years, outstanding performances of elderly people up to 100 years have been reported. In this case study, pacing during and recovery after a 12-hour ultra-marathon were described for a 95-year old runner. The athlete achieved a total distance of 52.987 km. Pacing followed a parabolic pattern (U-shaped), where the speed decreased till the middle of the race and then increased. However, no end spurt was observed. A large main effect of lap quartile on speed was observed, where the second quartile was slower than the first quartile and forth. The smallest variability was shown in the first quartile and the largest in the second quartile. During recovery, erythrocytes, hemoglobin and hematocrit increased whereas thrombocytes and leucocytes decreased. CRP, GOT, GPT, y-GT, CK, and LDH were increased post-race and decreased to reference range during recovery. Also, creatinine and urea decreased during recovery. Creatinine clearance increased during recovery. Sodium increased during recovery and remained constantly within the reference range. During recovery body fat and visceral fat mass decreased, whereas body water and lean body mass increased. In summary, a 95-year-old man was able to run during 12 hours using a U-shaped pacing and achieving a total distance of nearly 53 km. Increased selected haematological and biochemical parameters returned to pre-race values within a recovery phase of five days.